The failure arc paths of the novel device combining an arrester and an insulator under different pollution levels. (February 2021) - Qiao, Xinhan; Zhang, Zhijin; Sundararajan, Raji; Jiang, Xingliang; Hu, Jianping; Fang, Zhen
Highlights: The structure of the novel insulator combined with an arrester was introduced. The arc path tests under both AC and impulse voltage were conducted. Base on the arc paths recorded by a high-speed camera, 14 types of arc paths were defined. The statistical probability of each arc path under impulse voltage was calculated. The impulse voltage waveform corresponding to the typical arc path were presented and discussed. Abstract: Lightning strokes on transmission lines could trigger insulation failure if no protective measures are taken. Typically, a lightning arrester is used for this purpose. In order to combine the insulator and the lightning arrester as a single entity, a novel lightning protection composite insulator, combining an arrester and an insulator was developed for 10 kV distribution lines. Studied in this paper are the various arc paths of the novel insulator. The arc path tests under both AC and impulse voltage were conducted. The findings indicate that low, medium, high, very high, and extremely heavy pollutions caused different types of arcings under AC voltage. In addition, arc paths were affected by both the pollution level and the magnitude of impulse voltage. Based on the arc paths recorded by a high-speed camera, the flashover modes can be divided into three categories (flashover of the air gap, flashover of silicone rubber sheds in insulation section, and flashover of the whole insulator). More specifically, we defined and analyzed 14 types of arc paths in detail, and the critical pollution level (0.1 mg/cm 2 ) of normal operation were obtained. Further, the statistical probability of each arc under impulse voltage was calculated. Due to the complexity of the arc paths under the switching impulse voltage, a 90% probability distribution figure of arc paths with different Us (switching impulse voltage) and ESDD (equivalent salt deposit density) was presented according to the test results. At last, we discuss the impulse voltage waveform corresponding to the typical arc path and describe the research prospect. The research results in this paper present the failure modes of the novel lightning protection insulator, and the results can be used for designing insulators for various pollution levels.